Peran Guru sebagai Fasilitator dalam Menerapkan Pembelajaran Teks Eksplanasi di Sekolah Dasar - Melany, Pupu Imelda; Azzahra, Annisa Alifia; Rahmadanti, Intan; Julianto, Indra Rasyid (Jurnal Cahaya Edukasi, 2025)
This study aims to analyze the teacher's role as a facilitator in implementing explanatory text learning in elementary schools. In this subject matter, teachers are not only responsible for delivering lessons but also serve as mentors and facilitators to guide students in understanding concepts and composing explanatory texts independently. The research employed a qualitative approach through observations, interviews, and document analysis. The results indicate that the teacher's role as a facilitator includes providing relevant teaching materials, utilizing interactive and engaging teaching methods, and creating an attractive and conducive learning environment to encourage active student participation. Other methods employed by teachers involve group discussion strategies, the use of learning media, and providing feedback to enhance students' understanding of the structure and content of explanatory texts. In conclusion, the teacher's role as a facilitator significantly impacts students' abilities and development in understanding and composing explanatory texts. The implications of this study emphasize the importance of professional training and development for teachers to enhance the effectiveness of explanatory text learning at the elementary school level.